Professors as Intellectuals in China: Political Identities and Roles in a Provincial University. (17th November 2016) - Hao, Zhidong; Guo, Zhengyang
Abstract: Under Xi Jinping's administration, ideological control in China has been tightened and political dissent has become increasingly difficult, especially in universities. What can professors do? Our research in one university in central China finds that professors have multifaceted identities and engage in synchronous political roles as establishment/organic, non-establishment/professional and contra-establishment/critical intellectuals, although most take on the first two roles. Our research is based on 36 interviews with professors, students and administrators from various departments of this provincial university and on an analysis of the faculty's teaching and research. This paper aims to contribute to the sociology of intellectuals and higher education by illuminating how professors, as intellectuals, engage in contemporary Chinese political discourse. 摘要: 今天的中国已经进入了习近平时代, 意识形态的控制在进一步加强, 政治异议, 尤其是大学里的政治异议, 变得越来越艰难。在这种情况下, 作为知识分子的教授们能够做什么呢? 本文探讨中国中部地区的一所大学的情况。我们发现教授们有多重认同, 并同时扮演不同的政治角色, 包括体制"内"/有机角色、体制"外"/专业角色、"非"体制/批判角色 (具体定义请看内文)。多数人、多数情况下在扮演着前两种角色。我们的研究建立在对内地一所省属大学来自不同单位的 36 位教授、学生与行政领导的访谈以及对教授们的教学和研究的分析之上。希望我们的研究能够帮助人们理解作为知识分子的教授们是否以及如何与当代中国的政治对话。也希望本文能对知识分子社会学、高等教育社会学有所贡献。